External parameters of wireless power transmission systems - Грецких, Д.В.; Лихограй, В.Г.; Щербина, А.А.; Гомозов, А.В. (Radiotekhnika, 2019)
It is substantiated that for the analysis and optimization of wireless power transfer systems (WPT), which use various energy transfer technologies (rectenes can work in different modes, can be located in the near, intermediate and far zones of electromagnetic radiation sources, etc.), it is possible to apply a universal computational algorithm based on a nonlinear mathematical model of the electrodynamic level of the WPT system. According to this model the entire WPT system is considered as a single multi-input antenna system, which includes elements with nonlinear characteristics. Such a representation of the WPT system allows one to describe fully the electrodynamic processes taking into account the entire set of nonlinear effects that occur in the system itself, as well as the effects that are formed due to off-system interactions, i.e., the electrodynamic interaction of the WPT system with other electronic systems and vice versa. The output equations of the WPT system were obtained by which its parameters were determined that describe off-system interactions and intrasystem processes. It is shown that under designing WPT systems it is necessary to take into account the fact that not only the sources included in the WPT system, but also the sources from external radioelectronic means, as well as the fields arising from nonlinear transformations that are determined by the state variable vector.